Konsep Cyber Attack, Cyber Crime, Dan Cyber Warfare Dalam Aspek Hukum Internasional - Miko Aditiya Suharto; Maria Novita Apriyani (Jurnal Risalah Hukum, 2021)
The movement of human activities initially carried out conventionally turned into digital. This phenomenon also applies to the flow of information traffic. Information that was previously disseminated conventionally has become digitalized. Once the exchange of information and activities on the Internet is so widespread, it is as if the Internet is a world of its own with no boundaries. As a new dimension like land, sea, air, and space, Cyber space also has many problems related to the misuse of computer and internet technology for purposes that deviate from legal norms to the detriment of other parties. The implications of Cyber attacks have destructive properties such as changing, disrupting, closing access, reducing performance, or damaging computer files, computer networks, or the computer itself when associated with the rights of someone in the use of computer technology. This study uses normative research using a conceptual approach, a comparative approach, and a statutory approach. The results of this study are that the concepts and elements of cyber attack, cyber crime, and cyber warfare have differences. Cyberattack is a method used to carry out attacks using computer technology and the Internet. Cyber crime is a form of crime committed by utilizing computer and internet technology in carrying out crimes. Meanwhile, cyber warfare is a form of cyber operations (cyber operations) in an attack or defense, which is carried out to cause injury or death to people or damage or destruction of the target object or target operation.